Hopes and Challenges of Filipino Displaced Workers at This Covid- 19 Pandemic Period - QUIERREZ, JESSIE I.; ALCARAZ, LEO G. (The journal of contemporary issues in business and government, 2021)
Hopes and challenges were the focus of this study as it aimed at understanding the self-efficiency of Filipinos who were displaced at this pandemic period. Respondents were randomly taken from unaccounted pool of motor rider agents in Metro Manila and requested to respond on the survey provided to them. Results showed that in terms of hopes, Filipino- respondents Strongly Agree that they are dynamic, adaptable, and optimistic to surpass any difficulty and are very much hopeful that they will survive the challenges brought about by this Coronavirus pandemic. Likewise, when it comes to challenges, Filipino-respondents Strongly Agree that they are ready to solve difficult problems in terms of financial, health, food sustainability, spiritual/religious, and family social factors. Researchers therefore assumed that it is more than enough to say that combining the results achieved on the hopes and challenges of these Filipino-respondents, there is a strong basis that Filipinos are very much self-efficient as well as resilient as it is an innate characteristic on them with the influence of the environment and stimuli where they grow and their behaviors were molded to become better members of the society who are efficient, adaptable, ready to face the challenges, and hopeful amidst this pandemic period. This study also hope to possibly eliminate the notion about Filipinos negative values and instead strengthen and highlight the positive values that Filipinos are known for in the world which will bring constructive impact to those badly affected by the Coronavirus pandemic.